Von Transzendenz zum Transhumanismus. Deutungskulturen von (Un-)Heilsgeschichte im 19. und 20. Jahrhundert

Propagation of Chaos and Residual Dependence in Gibbs Measures on Finite Sets - Jalowy, Jonas; Kabluchko, Zakhar; Löwe, Matthias (Mathematical Physics, Analysis and Geometry)
Abstract We compare a mean-field Gibbs distribution on a finite state space on N spins to that of an explicit simple mixture of product measures. This illustrates the situation beyond the so-called increasing propagation of chaos introduced by Ben Arous and Zeitouni [3], where marginal distributions of size $$k=o(N)$$ k = o ( N ) are compared to product measures.

Optimal transport of stationary point processes: Metric structure, gradient flow and convexity of the specific entropy - Erbar, Matthias; Huesmann, Martin; Jalowy, Jonas; Müller, Bastian (Journal of Functional Analysis)

Comparative Analysis of Evolutionary Algorithms for Energy-Aware Production Scheduling - Burmeister, Sascha Christian; Rogalski, Till Niklas; Schryen, Guido

„Religiöse Gewalt“ in der Frühen Neuzeit? Eine begriffsgeschichtliche Revision - Süßmann, Johannes (Religiöse Gewalt in historischer Dimension)
In this chapter the common parlance of “religious violence in early modern history” is put to the test, although it seems to be linked in an indissoluble way with the master narratives about this period. The first section shows that it makes no difference whether historians think of early modern history in terms of impersonal structures or of personal experience–they agree in regarding religion as a crucial cause of violence. Against this widespread conviction the paper unfolds two arguments. The first is that the Latin word “religio”, as it was used throughout the 16th and 17th century, did not mean ‘religion’ in our modern comprehensive understanding of the word. Instead its meaning was quite narrow and specific, referring either to the medieval sense of ‘committing oneself to God by joining a religious order’ (becoming a “religiosus” resp. a “religiosa”) or to the ancient sense of ‘scrupulously venerating God’. It did not mean ‘faith’, ‘doctrine’, ‘worship’, ‘church law’ or ‘denomination’, and definitely not all these things in conjunction. Only when the vernacular languages began to borrow the Latin word from the 16th century onwards was its narrow meaning broadened. As a consequence of reformation and counterreformation, the idea arose that one should make faith and doctrine and worship and church law match, although the attempt to implement this new rapport provoked much opposition and turned out to be a very violent process. From this point of view what is generally called “early modern religious violence” is violence caused not by religion, but by the ambition to establish a new idea of religion. The second argument is that our modern understanding of religion is coined by the 18th-century critique of religion. Only the Enlightenment’s claim to overcome religion (in the new sense of the word) declared it to be “irrational” or even “fanatic”. Thus the Enlightenment invented religious fanatism, using it as a retrospective explanation of the violence that had gripped the last centuries. Modern parlance of “religious violence” unintentionally prolongs a very poor idea of religion–and one that should not be mistaken for an explanation.
Keywords: Religion; Gewalt; Begriffsgeschichte; Frühe Neuzeit; Aufklärung; Religionskritik

Unternehmensbewertung als Verknüpfung von Investitions- und Finanzierungsprogramm - Uhde, André (Unternehmerische Finanzierungspolitik – eine wertorientierte Einführung)

Ermittlung der Kosten des Eigen- und Fremdkapitals - Uhde, André (Unternehmerische Finanzierungspolitik – eine wertorientierte Einführung)

Relevanz und Wertbeitrag der Kapitalstruktur - Uhde, André (Unternehmerische Finanzierungspolitik – eine wertorientierte Einführung)

Wirtschaftswissenschaftliche Forschungsrichtungen vor der Neoklassik - Uhde, André (Institutionenökonomie und Betriebswirtschaftslehre)

Grundlagen der Principal-Agent-Theorie - Uhde, André (Institutionenökonomie und Betriebswirtschaftslehre)

Unternehmerische Finanzierungspolitik - Eine wertorientierte Einführung

Determination of the unit cell geometry in fibre-reinforced polymer sheets using guided acoustic waves - Wippermann, Mareen; Claes, Leander; Brandes, Philipp; Moritzer, Elmar; Henning, Bernd
Woven fibre-reinforced polymers are used in a variety of application, especially where a low mass to stiffness ratio is required. Of paramount importance for the tailored mechanical properties these composite materials exhibit is the type and geometry of the fibre weave. Especially continuous fibre-reinforced thermoplastic composites are fabricated as laminates and subsequently exposed to forming processes which alter the geometry of the fibres unit cell and thus the local mechanical properties of the material. An approach utilising broadband ultrasonic waves is proposed to non-destructively determine the geometry of the unit cell of the weave. The dispersive behaviour of woven fibre-reinforced sheets is described in accordance with the Flouquet-Bloch theorem as a phononic crystal. In order to develop a model for a description of these periodically structured waveguides, the smallest repeating unit of the wave is modelled with periodic boundary conditions. The resulting dispersion diagram exhibits similarities to that of a homogeneous plate, but additionally displays a periodicity in the wavenumber regime, which correspond with the size of the unit cell. Experimental studies of the dispersive behaviour of acoustic waves in woven fibre-reinforced samples also show a periodicity in the wavenumber regime, enabling a measurement procedure of the unit cell geometry.

Aspekte des Zusammenlebens zwischen Muslimen und Nichtmuslimen - Kokew, Stephan Matthias (Islam II. Regionen, Lebensformen, Geistesgeschichte)
Keywords: Islam; Islamwissenschaft; Toleranz; Islamische Geistesgeschichte; Interreligiöser Dialog

Assessment of Fibre-Matrix Adhesion in Reinforced Polymers by Modal Damping of Guided Acoustic Waves - Claes, Leander; Zeipert, Henning; Brandes, Philipp; Moritzer, Elmar; Henning, Bernd

Zeit für Arbeitszufriedenheit? Eine quantitativ-empirische Studie zur Bedeutung fester Kooperationszeiten für die Arbeitszufriedenheit von Lehrkräften in inklusiven Schulen - Wohnhas, Verena; Neumann, Phillip; Lütje-Klose, Birgit (QfI - Qualifizierung für Inklusion. Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)
Die Arbeitszufriedenheit von Lehrkräften gilt als zentrale Komponente für die Qualität des Bildungssystems. In inklusiven Schulen müssen Regelschullehrkräfte und sonderpädagogische Lehrkräfte kooperieren, um allen Schüler:innen eine bestmögliche Förderung zu gewährleisten. Dazu benötigen sie jedoch Zeitfenster, die von vielen Lehrkräften als nicht ausreichend benannt werden. Ziel des vorliegenden Beitrags ist es, empirisch zu untersuchen, welche Bedeutung festen Zeitfenstern für die Lehrkräftekooperation im Klassenteam, im Jahrgangsteam und im Fachteam für die Arbeitszufriedenheit zukommt. Weiterhin soll überprüft werden, ob Teile der Zusammenhänge über die Zufriedenheit mit der Kooperationshäufigkeit und die kollektive Selbstwirksamkeitsüberzeugung der Lehrkräfte erklärt werden können. Dazu werden Daten aus dem BMBF-geförderten Projekt BiFoKi mit N=194 Lehrkräften und N=28 Schulleitungen analysiert. Die Ergebnisse zeigen, dass feste Zeitfenster für die Kooperation in den unterschiedlichen Teams mit einer erhöhten Arbeitszufriedenheit im Zusammenhang stehen und in Teilen über die kollektive Selbstwirksamkeitsüberzeugung mediiert werden.
Keywords: Arbeitszufriedenheit; Inklusion; Sonderpädagogik; Kooperation; Selbstwirksamkeit; Schulentwicklung; job satisfaction; Inclusion; Special Education; Self-efficacy; school development

Digitale Medien in der Lehrer-Schüler-Interaktion - Herzig, Bardo (Lehrer-Schüler-Interaktion. Inhaltsfelder, Forschungsperspektiven und methodische Zugänge)

Psychologiedidaktik an allgemeinbildenden und beruflichen Schulen

Sustainability, Climate Change and Convention Theory - Lenz, Sarah (Handbook of Economics and Sociology of Conventions)

„The folk songs of America“ und „complex female characters on stage“: Musikgeschichtliche Wendepunkte in den Komponistinnenbiografien von Florence Price and Mizzy Mazzoli - Tumat, Antje (her:voice. Komponistinnenfestival 2024)

Empirische Methoden der psychologiedidaktischen Forschung - Scharlau, Ingrid; Seifert, Andreas (Psychologiedidaktik an allgemeinbildenden und beruflichen Schulen: Ein Lehrbuch mit Unterrichtsmaterialien)